High Rate of Living Kidney Donation to Immigrant Children Despite Disparities—An Epidemiological Paradox? - Oztek-Celebi, Fatma Zehra; Herle, Marion; Ritschl, Valentin; Kaltenegger, Lukas; Stamm, Tanja; Aufricht, Christoph; Boehm, Michael (Frontiers in Pediatrics, 2019)
Background: Kidney transplantation is the preferred treatment modality for children with end-stage renal disease. In the adult population, migration-related modifiable factors were associated with low living donation rates; no such data are available on the pediatric population. This pilot study therefore compares donation modality, communication, knowledge, and attitudes/beliefs between families of immigrant and nonimmigrant descent. Methods: Demographic and clinical characteristics of a cohort of children from 77 families of immigrant (32; 42%) and nonimmigrant (45; 58%) descent who had undergone renal transplantation were assessed and related to donation modality at the Medical University Vienna. In a representative subset, modifiable migration-related factors were assessed in a questionnaire-based study. Results: In immigrant families, information delay, limited communication, low knowledge levels and self-reported conflicting beliefs were significantly more prevalent than in nonimmigrants. The living kidney donation rate to children was high in both populations (immigrants: 63%, nonimmigrants: 44%; p=0.12). Living donation to children on dialysis was even significantly higher in immigrant families (immigrants: 13 out of 20; 57%, nonimmigrants: 9 out of 33; 27%; p=0.03). Conclusion: Contrary to expectations, migration-related disparities did not translate into decreased living donation rates in immigrant families, in particular to children on dialysis. Certain factors might therefore be less important for the living donation process in pediatric care structures and/or might be overcome by yet undefined protective factors. Larger pediatric studies including qualitative and quantitative methods are required to validate and refine current conceptual frameworks integrating the perspective of affected families.